Breaking the impasse: the case for establishing a no first nuclear threat norm - Cormier, Monique; Hood, Anna (Journal on the use of force and international law, 2024)
For more than half a century, non-nuclear weapon States have sought to outlaw nuclear threats. Across the decades, some of the nuclear armed States have issued assurances and/or signed agreements limiting their recourse to nuclear threats. Many of these assurances and agreements have, however, contained reservations that limit their scope. Further, there is debate as to whether some of the assurances given are legally binding. The piecemeal state of assurances and agreements on nuclear threats has allowed nuclear armed States to issue nuclear threats on a concerningly frequent basis. In this article, we consider the idea of developing a non-binding no first threat norm whereby nuclear armed States would commit to not being the first to make nuclear threats. We suggest that this norm should encompass both specific threats and general nuclear threats, and that it should be made to both non-nuclear weapon States and other nuclear armed States.